Who Answers the Call? Plural Selves, Internal Publicness, and Subjectifying Education - Oyler, Joe (Philosophical Inquiry in Education, 2026)
In this article, I take a critical stance against the individualist and essentialist conceptions of self embedded in educational policy and practice in the contemporary west and global north. These conceptions are both historically rooted in a colonial conception of “man” as rational and independent and are explanatorily narrow, failing to account for the relational and plural nature of lived subjectivity. To envision an alternative, I draw from the decolonial feminist phenomenology of Mariana Ortega and Maria Lugones and on Kathleen Wallace’s Cumulative Network Model—an account of selves as historically cumulative networks of “I” perspectives. I argue that reflexive dialogue among these perspectives exhibits an internal publicness that extends Biesta’s conception of becoming public beyond its social orientation. Drawing on Valsiner and Cabell’s catalysis metaphor and the practice of Philosophy for Children, I propose pedagogical mechanisms that support both external dialogue among students and internal dialogue within their network selves. Reclaiming the publicness of education, I conclude, requires cultivating publicness not only between persons but within them.